2023
DOI: 10.3390/en16020675
|View full text |Cite
|
Sign up to set email alerts
|

Organic and Inorganic Biocidal Energetic Materials for Agent Defeat Weapons: An Overview and Research Perspectives

Abstract: A critical survey concerning biocidal energetics is proposed according to a classification depending on their chemical structure. The need of optimizing the performances of such compounds is an important target for the inertization of biological weapons, requiring a synergy between the thermal effects of combustion/detonation with the biocidal effects of reaction products released into the environment. The main physicochemical aspects related to the synthesis technique, the thermodynamic variables and the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 181 publications
0
6
0
Order By: Relevance
“…Solid propellants and explosives with much higher energy performance are urgently needed in modern national defense technology [ 1 , 2 ]. Metal fuels have the advantages of high energy density [ 3 ], high combustion calorific value [ 4 ], and high-frequency combustion stability [ 5 ]; therefore, they have been widely used as high-energy additives to improve the energy density of energetic formulation systems [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid propellants and explosives with much higher energy performance are urgently needed in modern national defense technology [ 1 , 2 ]. Metal fuels have the advantages of high energy density [ 3 ], high combustion calorific value [ 4 ], and high-frequency combustion stability [ 5 ]; therefore, they have been widely used as high-energy additives to improve the energy density of energetic formulation systems [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, boron is considered one of the most promising metal fuel additives in solid propellants [19]. In recent decades, research results have shown that three important problems have limited the application of boron [20,21], which can be summarized as follows: (1) the ignition performance is poor due to the protective oxide layer on the surface of boron powder, which thickens gradually during combustion, and resulting in a longer ignition delay time; (2) the low melting point (718 K) and high boiling point (2316 K) of B2O3 facilitate the formation of a liquid film, which attaches on the surface of boron particles during combustion, and thus hinders the diffusion of oxygen and reduces the combustion efficiency of boron (both melting point and boiling point of pure boron >2500 K) [22,23]; (3) impurities such as B2O3 and H3BO3 can react with the hydroxyl of hydroxyl-terminated polybutadiene (HTPB) and form a gel layer on the surface of boron powder, which results in poor compatibility between boron and HTPB [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Designing tEMs with different novel microstructures and improving the energy-releasing capacity of tEMs have been two of the most essential research focuses, and the corresponding amount of important literature regarding tEMs is growing fast. In fact, some reviews are available for energetic materials [ 39 , 40 , 41 ]. For example, Y.M.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-weapons are easy to manufacture and release, and hazards caused by such weapons will increase exponentially after leaks [1,2]. Thus, the best way to defeat bio-weapons is to destroy bio-agents instantly at the factory or storage.…”
Section: Introductionmentioning
confidence: 99%